HIGH STRENGTH CONCRETE USING FLY ASH A CEMENT AND FINE AGGREGATE - Bachtiar, Erniati; Setiawan, Arman; Musahir, Fajar (Universitas Ibn Khaldun Bogor, 2022)
At the moment, the cost of concrete is quickly increasing as the cost of cement and aggregates continues to rise. As a result, a replacement for fine aggregate as well as a substitute for cement is required to decrease the cost of concrete production. In general, concrete is composed of cement as a base material that is workable and satisfies specified performance, durability, and strength criteria, aggregate, and water. In the field of engineering constructions, reinforced high-strength concrete has a significant impact on development. Apart from its exceptional strength, this kind of concrete must exhibit workability, minimal shrinkage, release characteristics, and self-compaction. The authors of this research performed a literature review to explore high-quality concrete made using fly ash as a replacement for cement and fine particles. Fly Ash is a waste product or byproduct of the coal-fired power plant's combustion process. Fresh concrete made using fly ash as cement and fine aggregate has an average slump value of 90-200 mm. The compressive strength of concrete made with fly ash ranges between 35 and 60 MPa after a 28-day curing period. The optimal percentage of fly ash in high-strength concrete is between 10% and 30%.